The Great Wheel / The World Monetary System - Burtle James; Rolfe Sidney E (Quadrangle, 1973)
This book examines the economic crises of 1971 and outlines a new and constructive policy for international economic cooperation in the seventies. Introduction, Before World War II, The Money Machine, The Interwar Years: Beggar Whose Neighbor?, The Gold Exchange Standard and After, Some Conclusions, The Rise and Fall of the Bretton Woods System, The Bare Bones of Bretton Woods, 1949-1958: Beneficial Disequilibrium, 1958-1965: Revelation, 1965-1971: Disintegration, Transition, Reform, Capital Flows: Eurodollars, The Political Economy of World Money: Mercantilism Revisited, Keeping Afloat, How Business can Live the System, Forecasting Foreign Exchange Rates, The Politics of Exchange Rate Forecasting, Appendix, Bibliography, Index.